Indispensable when leaders really matter - Mukunda, Gautam (Boston, Mass. Harvard Business Review Press, 2012)
The importance of leadership and the impact of individual leaders has long been the subject of debate. Are they made by history, or do they make it?
Includes bibliographical references (p. 275-289) and index.
Keywords: Leadership